A Jurisprudential Analysis of the Ammatoa Indigenous People's Legal Rights over the Management of Customary Forests in Bulukumba - Samad, Ansyaruddin; Rifdan, Rifdan; Dhahri, Irsyad (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The Ammatoa Kajang indigenous community is a group that has lived for generations within the Kajang customary area, holding sovereignty over their land and natural resources, and regulating their socio-cultural life based on customary law and the traditional institution of "Pasang ri Kajang." Research has shown that indigenous communities in Indonesia have traditionally succeeded in preserving and enriching the biodiversity of nature. The Ammatoa Kajang community has autonomy in managing their customary forest. The research method used is descriptive qualitative with a sociological legal approach aimed at gaining legal knowledge. It begins with secondary data as initial information, followed by primary data gathered from the field or the community, studying the effectiveness of a regulation, and seeking to explore the relationship between various phenomena. Data collection tools include document studies or literature reviews and interviews. The research findings show that Ammatoa, as the head of the Kajang indigenous community, emphasizes the importance of prioritizing customary law in every aspect of the Kajang indigenous people's lives, including in resolving issues within the community. The Ammatoa Kajang community resolves and defends their customary territory using customary law as outlined in “Pasang ri Kajang.” Sociological Jurisprudence views law as a living part of society, continually adapting to social changes and the needs of its people, while still being rooted in shared communal values